2012
DOI: 10.1007/s10862-012-9275-8
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Relationships among Negative Affect, Difficulties in Emotion Regulation, and Features of Borderline Personality Disorder

Abstract: This study investigated the indirect effects of problematic emotion regulation on features of Borderline Personality Disorder (BPD) when accounting for negative affect in 456 participants from two distinct geographic regions. Participants completed the Affect Intensity Measure (AIM), Difficulties in Emotion Regulation Scale (DERS), the Emotion Regulation Questionnaire (ERQ), and the Borderline Symptom List (BSL). Results from this study supported a model in which there were significant indirect effects of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 32 publications
8
88
0
1
Order By: Relevance
“…Consistent with this notion are studies indicating that higher self-reported and clinician-rated levels of BPD symptoms are associated with a lower frequency of using cognitive reappraisal, problem-solving, and acceptance [26-30]. Associations have also been found between higher BPD symptoms and more frequent utilization of suppression, rumination, and avoidance [9, 10, 31-34].…”
Section: Introductionmentioning
confidence: 81%
“…Consistent with this notion are studies indicating that higher self-reported and clinician-rated levels of BPD symptoms are associated with a lower frequency of using cognitive reappraisal, problem-solving, and acceptance [26-30]. Associations have also been found between higher BPD symptoms and more frequent utilization of suppression, rumination, and avoidance [9, 10, 31-34].…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, future studies should examine potential moderators on emotional recovery in BPD. Both “maladaptive” (i.e., disordered eating and substance abuse; Sansone, Chu, Wiederman, & Lam, 2011) and “adaptive” (i.e., cognitive reappraisal; Salsman & Linehan, 2012) BPD-relevant behaviors should be assessed, as they may shed light on what HCs do to facilitate emotional recovery that individuals with BPD may not do, and whether BPD-relevant maladaptive behaviors function to facilitate emotional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…BPD has been conceptualized as chronic emotion dysregulation; individuals with BPD or high in BPD features demonstrate the tendency to respond to negative emotions with numerous maladaptive strategies (Salsman & Linehan, 2012;Selby, Anestis, Bender, & Joiner, 2009). These include behaviors, such as impulsive and self-destructive actions (Bornovalova et al, 2005;Gratz, Breetz, & Tull, 2010; and avoidance of goal-directed behavior (Gratz, Rosenthal, Tull, Lejuez, & Gunderson, 2006), as well as cognitive processes, such as rumination (Baer & Sauer, 2011) and decreased present-centered awareness and acceptance .…”
Section: Dysfunctional Responses To Emotion Mediate the Cross-sectionmentioning
confidence: 99%